2008
DOI: 10.1007/s10551-008-9860-7
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Structures and Processes of Corporations Operating in Australia, Canada, and Sweden: A Longitudinal and Cross-Cultural Study

Abstract: codes of ethics, cross-cultural, empirical, ethical structures and processes, longitudinal, Australia, Canada, Sweden,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
0
11
0
2
Order By: Relevance
“…Svensson et al . () found that corporations operating in Sweden have utilized ethical structures and processes differently from their Canadian and/or Australian counterparts, and that in each culture the way in which companies fashion their approach to business ethics appears congruent with their national cultural values. Ringov and Zollo () suggest that national culture dimensions have a strong impact on the CSR behavior of organizations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Svensson et al . () found that corporations operating in Sweden have utilized ethical structures and processes differently from their Canadian and/or Australian counterparts, and that in each culture the way in which companies fashion their approach to business ethics appears congruent with their national cultural values. Ringov and Zollo () suggest that national culture dimensions have a strong impact on the CSR behavior of organizations.…”
Section: Methodsmentioning
confidence: 99%
“…Given the growing importance that CSR has on the management and strategy of the company (Carroll and Shabana, 2010), some authors have empirically studied the strong impact that cultural characteristics of countries have on the socially responsible behaviour of their companies (Waldman et al, 2006;Ringov and Zollo, 2007). Others have focused on the differences between countries (Singh et al, 2008;Yong, 2008;Svensson et al, 2009). Therefore, based on institutional theory (Baughn et al, 2007;Matten and Moon, 2008), the CSR concept is different according to the country (Jamali and Mirshak, 2006) and the expectations of the different stakeholders should be alike in countries with similar cultural characteristics.…”
Section: Ebate Is Growing About the Lack Of Agreement On The Relatimentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting evidence for the effect of national culture on CSR was the work of Svensson et al (2009) which explored a difference in the ethical behavior of corporations in Australia, Canada, and Sweden over two time periods (2001-2002 and 2005-2006). The findings revealed that there was a variation of ethical corporate behaviors among corporations in different countries and concluded that the way in which corporations outlined their approach to business ethics depended on national cultural values where the corporations operated.…”
Section: National Culture and The Literature On Corporate Social Respmentioning
confidence: 99%
“…North (1990) assinalou que os países desenvolvidos são fortemente dependentes de regras formais e menos dependentes de restrições informais. Svensson et al (2009) constataram que o Canadá apresenta um alto nível de normas formais estabelecidas, estando suas empresas sujeitas a um sistema mais regrado. Schmidheiny (2006) salientou que o engajamento social reforça a identificação das empresas brasileiras como "uma contribuição significativa para a solução dos problemas sociais do país".…”
Section: Discussionunclassified